(untitled) (Journal of the College of Education for Women, 2019)
The current research aims to :•know the level of the chaotic behavior of the sample as a whole .•Know the differences with statistical significance in disorderly behavior between thedisadvantaged and non-disadvantaged peers .To achieve these objectives, the selected sample of Talbhalmrahlh medium and specificallystudents of the second grade average, were chosen randomly stratified’s (360) studentsincluded sex (male, female) and (deprived of the Father and the non-deprived) for theacademic year (2013-2014) to the province Baghdad on both sides (Rusafa-Karkh (As applied to them measurements of disorderly behavior, which is prepared by the researcher,having achieved _khasaúsma of psychometric (valid and reliable .)When analyzing the data were used statistical methods, both when extracting multiplepsychometric properties, crashes or achieve the objectives of the research, including (Pearsoncorrelation coefficient, and the equation Alvakronbach and samples t-test for one sample andsamples t-test for two independent samples .The researcher found the following results :•When members of the research sample behavior messy low .•The existence of statistically significant differences in disorderly behavior amongadolescents deprived of their parents and their peers who live with their parents, and for thebenefit of disadvantaged parents, that is deprived of parents is more chaotic behavior ofchildren deprived of others .In light of the findings of the researcher made a number of recommendations and suggestions .